Influence of Urban Street Vending on Pedestrian Experience and Behaviour: A Systematic Quantitative Review - Jacob, Amala Anna (Alanya Üniversitesi, 2023)
Urban street vending is an integral part of everyday public life and can contribute to vibrant and lively streets. Yet, few cities formally integrate this activity into public space design. This is because street vending is a highly contested, although transformative phenomenon that has complex inter-relationships with other urban entities. This paper systematically and quantitatively assesses the breadth and depth of academic literature that studied such a relationship; more specifically, the influence of street vending on pedestrians' experiences and behaviours and thereby identifies gaps in the existing literature. A systematic review of 25 peer-reviewed journal articles is undertaken to provide an assessment of the geographic extent, disciplinary scope, timeline of publications, keywords, methods, theories, constructs and concepts. This review concludes that the existing research is emerging, but rapidly accelerating and cross-disciplinary. Although the research was predominantly conducted in the Global South, it is largely affiliated with the Global North with limited North-South partnerships. The literature is largely qualitative, indicating a propensity for skewed perspectives. It also lacks theoretical applications exclusive to pedestrian-vendor relationships. Finally, potential areas where future researchers may expand and influence the knowledge domain are identified. This includes developing multi-contextual global perspectives through North-South partnerships and combining or independently applying grounded theory, mixed methods and case study research to broaden theoretical and empirical bases.